2011
DOI: 10.1016/j.intimp.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mac-1 and VLA-4 integrins, and concomitant Th2-cytokine production, in nitric oxide modulated eosinophil migration from bone marrow to lungs in allergic mice

Abstract: Although numerous studies demonstrate the participation of nitric oxide (NO) in various inflammatory diseases, the precise function of NO in allergic asthma remains unclear. We investigated whether iNOS inhibition could interfere with the kinetics of VLA-4 and Mac-1 expression and adhesion properties of bone marrow and peripheral blood eosinophils of sensitized mice after antigen exposure. Treatment of allergic mice with 1400 W (iNOS inhibitor) increased the adhesion of bone marrow eosinophils to ICAM-1, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As a common upper airway inflammatory disease, AR is typically characterized by a predominant Th2 response and eosinophil infiltration in nasal mucosa [ 32 34 ]. NO was proven to be pivotal in modulating the production of Th2 cytokines which were responsible for the migration of eosinophils into the airway mucosa [ 35 ]. Prior publications demonstrated that nNO could be used as a reproducible and noninvasive biomarker in respiratory diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a common upper airway inflammatory disease, AR is typically characterized by a predominant Th2 response and eosinophil infiltration in nasal mucosa [ 32 34 ]. NO was proven to be pivotal in modulating the production of Th2 cytokines which were responsible for the migration of eosinophils into the airway mucosa [ 35 ]. Prior publications demonstrated that nNO could be used as a reproducible and noninvasive biomarker in respiratory diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…They localize close to sensory as well as parasympathetic neurons both in animal models of asthma and in biopsied lungs of asthma patients (223). In prurigo nodularis, a chronic skin disease characterized by nodules and intense itch, eosinophils are closely associated with CGRP + nociceptive fibers (224) and in atopic dermatitis patients eosinophils are more closely associated with nerve fibers than in healthy controls (225). Finally, although the identity of the neurons was not determined in this context, close nerve-eosinophil contact was also observed in the colon and Peyer's patches of rats infected with the parasite Fasciola hepatica (226).…”
Section: Eosinophilsmentioning
confidence: 99%
“…This same study also showed a dynamic expression of α 4 β 7 on eosinophils across different tissue contexts. The findings that eotaxin-1-induced eosinophil recruitment to the lung and eotaxin-1-mediated chemoattraction in vitro are dependent upon VLA-4 (α 4 β 1 ) (Kitayama et al, 1997) and that VLA-4 is dynamically modulated by allergen challenge (Pelaquini et al, 2011) suggest that the other α 4 -associated integrins on eosinophils (e.g., α 4 β 7 ) may also be involved in eotaxin-mediated events. Consistent with this possibility, there is delayed intestinal hypersensitivity (including lymphocyte and eosinophil infiltrations) in response to intestinal infection with Trichinella spiralis in β 7 -deficient animals (Artis et al, 2000).…”
Section: Eosinophil Adhesionmentioning
confidence: 99%